RETURNS TO EDUCATION IN EUROPE. SAME OR NOT? - Sylwia Roszkowska (European Scientific Journal, ESJ, 2014)
The main aim of the paper is estimation of the Mincer equation parameters for European countries. The Mincer equation describes the impact of years of schooling and the work experience to the wages. The estimates of that equation were obtained using crosssection data for selected European in 2002 and 2010. Obtained results show huge differences returns to education in European countries. It seems that countries with better labor market outcomes can be characterized by lower rates to education. The variation of estimated rates stayed unchanged in analyzed period.